Role of registry offices regarding the expiration of precautionary measures according to Law 1579 of 2012 - Uribe Marín, Juan David (Multidisciplinar (Montevideo), 2024)
In the context of Colombian legislation, the registry offices of public instruments play a role of significant relevance. These offices operate as intermediaries for the materialization of the transfer of real estate, pursuant to Article 756 of the Civil Code. In this analysis, we address the crucial role of the registry offices of public instruments in relation to the expiration of precautionary measures, framed in Article 64 of Law 1579 of 2012. Since more than ten years have passed since the implementation of this provision, the processes involving the renewal of precautionary measures have been addressed in correspondence with the interested parties and their legal representatives. In order to understand this approach, a methodology based on documentary review has been adopted, analyzing relevant research on the subject. Through this analysis, it has been possible to corroborate the usefulness and relevance of forfeiture as it has been conceived in the legislation. It is evident that precautionary measures were designed with the purpose of ensuring compliance with judicial rulings, in response to a global reality in the field of the administration of justice: the time required to initiate, develop and conclude a legal process. In the Colombian context, this duration is excessive. However, these measures are essential to safeguard the results of judicial decisions and have been conceived as a response to the prolonged time involved in carrying out a legal process in various justice systems (Case T-356/18, Constitutional Court, 2018)